Determination of the Rate Constant on the Decrease of Iodate Content in Iodized Salt - Wisnu Cahyadi (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2006)
Potassium iodate used as the source of iodine can be decomposed to become the other species i.e. iodide and iodine during processing and storage. The objective of this research was determination of the rate constant on the decrease of iodate content in iodized salt. The method was used to determine the temperature and the length of storage effects on iodate stability in iodized salt. The research was obtained the rate constant on the decrease of iodate content in iodized salt (K) 2.55 x 10-8 ppm day-1 and energy of activation (Ea) 12.002 kcal mol-1 K-1. Key words : Postassium iodate stability, iodized salt and the rate constant on the descrease of iodate